Respostas metabólicas de plantas de arroz submetidas ao estresse salino - Cardoso, Lívia Leitão (2024)
Although plant responses to soil salinity have been investigated, little is known about how excess NaCl affects the metabolism of different plant organs. The aim was to investigate the effect of the saline stress on the growth and metabolic profile of different organs of rice plants. Rice plants grown in nutrient solution containing different doses of NaCl (0, 16, 25 and 50 mM) were used. Comparative analyzes of leaves, stem and root were carried out at ionic (Na+ and K+), metabolic and growth levels, using plant material collected from different parts of the plant. The data obtained were compared using analysis of variance and Tukey's test, as well as partial least squares discriminant analysis (PLS-DA). As expected, plants under saline stress contain higher concentrations of Na+ and a reduction in the K+/Na+ ratio in the root. Similar results were found in different portions of the stem (basal, middle and apex) and in the basal and middle leaves under almost all NaCl concentrations. However, there were no changes in the levels of Na+, K+ and the relationship between them in the apex leaves, flag leaves and panicles of the plant. Excess NaCl harms plant growth, evidenced by the lower biomass accumulated in the different organs of the plant as the NaCl concentration increases. However, only flag leaf biomass was lower under 16 mM NaCl when compared to control.The root was the organ that presented the lowest number of metabolites whose levels were significantly altered (only 4), when compared to the control. However, the metabolic profile of the root was the most discrepant among the organs, regardless of the presence or absence of stress. PLS-DA stated that the only treatment clearly separated from the control in different organs of the plant was 50 mM NaCl, although this separation was less evident in the panicle and flag leaf. Furthermore, under 16 mM salt stress, an interesting separation was observed, in which three main groups were formed, composed of root, panicle+stem and leaves. Under 25 mM NaCl, the flag leaves were grouped with the culms and panicle, and not with the leaves, while under 50 mM NaCl four groups were formed, composed of leaves, stem+panicle, root and flag leaf. The metabolic profile results show that there is a strong metabolic discrepancy between the different parts of the plant, which is independent of the presence of stress, but that excess NaCl accentuates these spatial differences in the plant. The ionic, metabolic and growth responses to salt stress vary strongly according to different shoot and root organs of the rice plant.